Association of dietary quality and mortality in the non-alcoholic fatty liver disease and advanced fibrosis populations: NHANES 2005–2018 - Huang, Xingyong; Zhang, Xiaoyue; Hao, Xuanyu; Wang, Tingting; Wu, Peng; Shen, Lufan; Yang, Yuanyuan; Wan, Wenyu; Zhang, Kai (Frontiers in Nutrition, 2025)
BackgroundNonalcoholic fatty liver disease (NAFLD) has emerged as a significant global health concern, with advanced fibrosis increasing mortality risks. Despite the abundance of dietary guidelines for managing NAFLD, the precise impact of diet quality on mortality among individuals with advanced fibrosis remains elusive. This study aims to explore the influence of five dietary quality indexes on mortality among NAFLD patients and advanced fibrosis patients.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning from 2005 to 2018 to assess dietary quality based on the Alternate Mediterranean Diet (aMED), Healthy Eating Index-2020 (HEI-2020), Dietary Approach to Stop Hypertension (DASH), Alternate Healthy Eating Index (AHEI), and Dietary Inflammatory Index (DII). Weighted Cox proportional hazard regression models along with restricted cubic splines and subgroup analyses were employed in this study.ResultsThe analysis encompassed 3,634 NAFLD patients. After a median follow-up of 89 months, it was found that higher scores on the aMED (HR 0.814, 95% CI 0.681–0.972), HEI-2020 (HR 0.984, 95% CI 0.972–0.997), DASH (HR 0.930, 95% CI 0.883–0.979), and AHEI (HR 0.980, 95% CI 0.966–0.995) were associated with lower mortality risks, while DII scores (HR 1.280, 95% CI 1.098–1.493) indicated an increased risk of mortality. Additionally, a nonlinear relationship was identified solely between AHEI scores and all-cause mortality in NAFLD patients. Notably, among patients with advanced fibrosis, HEI-2020 as a categorical variable (T3: HR 0.519, 95% CI 0.280–0.964), DASH as a continuous variable (continuous: HR 0.921, 95% CI 0.849–0.999), AHEI (continuous: HR 0.971, 95% CI 0.945–0.997; T2: HR 0.545, 95% CI 0.310–0.960; T3: HR 0.444, 95% CI 0.245–0.804), and DII (continuous: HR 1.311, 95% CI 1.121–1.534; T3: HR 2.772, 95% CI 1.477–5.202) exhibited significant associations with all-cause mortality. Subgroup analyses revealed an interaction between AHEI scores and sex among NAFLD patients, where higher AHEI scores correlated with lower all-cause mortality in females, but no such association was observed in males. For other dietary quality, subgroup analyses indicated that their relationships with mortality were robust.ConclusionOur study suggests that a high-quality diet could potentially mitigate mortality risk in both NAFLD and advanced fibrosis patients.